Tir Tyrosine Phosphorylation and Pedestal Formation Are Delayed in Enteropathogenic Escherichia coli sepZ::TnphoA Mutant 30-5-1(3) - Devinney, Rebekah (American Society for Microbiology, 2001)
Enteropathogenic Escherichia coli (EPEC) strain 30-5-1(3) has been reported to form attaching and effacing (A/E) lesions without Tir tyrosine phosphorylation. In this study, we show that 30-5-1(3), which has a transposon insertion within the sepZ gene, forms wild-type A/E lesions including Tir tyrosine phosphorylation, but at a slower rate. A/E lesion formation by 30-5-1(3) occurs without detectable secretion of Tir or other EPEC Esp secreted proteins.